Skills training in activities of daily living for persons living with dementia: a scoping review protocol - Keita Nakagawa; Takeshi Imura; Tsubasa Mitsutake; Junpei Tanabe; Ryo Tanaka (BMJ Open)
Introduction The need for rehabilitation interventions for persons living with dementia is increasing. Improvements in the activities of daily living (ADLs) are often required in this process. On the other hand, reduced learning ability among these people complicates decision-making regarding interventions, so research is needed to support this. Structured skills training is commonly used to teach ADLs to persons living with dementia, and studies have reported it to be useful. However, a synthesis of the evidence on this topic is lacking. Therefore, this scoping review aims to systematically integrate the results of randomised controlled trials (RCTs) on skills training for persons living with dementia, identify gaps in existing knowledge and suggest future research and practice.Methods and analysis This scoping review was planned based on the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) guidelines. We comprehensively searched target articles using five electronic databases (PubMed, Cochrane Central Register of Controlled Trials, Scopus, Physiotherapy Evidence Database and Cumulative Index to Nursing and Allied Health Literature) on 20 March 2024 and are currently screening their titles and abstracts. Eligible studies are RCTs published in English peer-reviewed journals that evaluated the results of skills training for ADLs in participants diagnosed with dementia. We are excluding studies that included mild cognitive impairment, used an intervention that is non-specific to ADLs and lacks teaching strategies, applied group settings, or addressed only smooth movement or stability. The search process and extracted data will be presented using structured figures and tables. By integrating and interpreting the findings, we will identify the gaps in the existing knowledge.Ethics and dissemination Ethical approval is not required for this study because the data will be collected from existing research articles. This scoping review will be disseminated through conference presentations and peer-reviewed journals.Trial registration number UMIN000054539.